DESAIN DIDAKTIS MENENTUKAN JARING-JARING BANGUN RUANG UNTUK MENGEMBANGKAN KEMAMPUAN REPRESENTASI SISWA KELAS V SEKOLAH DASAR - Haryani, Eni; Maulana, M.; Subarjah, Herman (Jurnal Pena Ilmiah, 2017)
Mathematical representation ability is needed in mathematics, so that the barriers that occur in developing the ability of student representation should be anticipated by the learning and teaching materials in accordance with characteristics of students tailored to the ability developed. This research uses the method of didactical design research (DDR) method. The purpose of this research is to make didactic designs based on the obstacles that arise in the implementation of preliminary study, and take the material of the spatial webs geometry and develop the ability of mathematical representation. In this study using realistic mathematics learning approach, in this approach students are required to find their own knowledge. This research focuses on the development of teaching materials in the form of student worksheets, in the student worksheets arranged based on obstacles that occur later then validated by experts, in addition to making teaching materials and learning implementation plan in this study also makes predictions of student responses and pedagogical didactic anticipation. The conclusions drawn from didactic design research to determine the spatial webs for developing mathematical representations of grade V elementary school students.